Study of the Synthesis Silver Nanoparticles and the Particle Size Effect on Surface-Enhanced Raman Scattering Spectroscopy of Methylene Blue - Hoang, Thi Thu Hoai; Hoang, Thi Linh; Nguyen, Huu Dong; Giap, Van Hung; Pham, Van Hai; Nguyen, Thi Tuyet Mai (Old Journal, 2019)
Surface-Enhanced Raman Scattering (SERS) is a modern technique that strongly enhances the Raman scattering signal of the analytes. The SERS phenomenon was explained by the localized surface plasmon resonance (LSPR) of the Raman substrate. In this report, silver nanoparticles one of the plasmonic structures were used to enhance the Raman signal of the methylene blue dye up to 10⁸ times. Especially, the highest Raman signal enhancement was observed when the plasmon resonance wavelength was close to the laser excitation wavelength. Thus, the silver nanoparticles-based SERS technique allows for the ultra-sensitive detection without destroying the sample which is suitable for point of care testing and biomedical analysis.